2021
DOI: 10.1093/rheumatology/keab680
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chronic immune-mediated inflammatory diseases after diagnosis with Kawasaki disease: a population-based cohort study

Abstract: Objectives Kawasaki disease (kDa) is an immune-mediated vasculitis of childhood with multi-organ inflammation. We determined the risk of subsequent immune-mediated inflammatory disease (IMID), including arthritis, type 1 diabetes, inflammatory bowel disease (IBD), autoimmune liver disease (ALD), primary sclerosing cholangitis (PSC) and multiple sclerosis (MS). Methods We conducted a matched population-based cohort study using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is debatable whether KD is postinfectious hyperinflammation, autoinflammatory, or autoimmune disorders [ 29 ]. After years of research, KD is considered an immune-mediated vasculitis [ 30 ]. Studies have found that T cells are mainly involved in KD's immune pathogenesis, including increased T cell activation and cytokine production, the proinflammatory (Th cells) and anti-inflammatory cells (Treg cells) imbalance [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is debatable whether KD is postinfectious hyperinflammation, autoinflammatory, or autoimmune disorders [ 29 ]. After years of research, KD is considered an immune-mediated vasculitis [ 30 ]. Studies have found that T cells are mainly involved in KD's immune pathogenesis, including increased T cell activation and cytokine production, the proinflammatory (Th cells) and anti-inflammatory cells (Treg cells) imbalance [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We considered the 30-day time point after KD diagnosis as the index date. To ensure that all of the included individuals had a new diagnosis of JIA, we excluded any pre-index-date diagnosis of JIA ( ICD-9-CM codes 714 and 720; ICD-10-CM codes M05, M06, M08, and M45) ( 14 ).…”
Section: Methodsmentioning
confidence: 99%